2004
DOI: 10.1136/adc.2003.036921
|View full text |Cite
|
Sign up to set email alerts
|

Twenty year surveillance of invasive pneumococcal disease in Nottingham: serogroups responsible and implications for immunisation

Abstract: Aims: To evaluate the incidence, spectrum of clinical manifestations, and outcome of invasive pneumococcal disease (IPD) in children. To determine the major serogroups of Streptococcus pneumoniae responsible for invasive disease and the potential coverage by the new pneumococcal conjugate vaccines. Methods: Analysis of prospectively recorded information of all children admitted to two teaching hospitals in Nottingham with IPD between January 1980 and December 1999. Results: A total of 266 episodes of IPD in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 33 publications
(34 reference statements)
5
45
0
2
Order By: Relevance
“…In a study by Fouda et al (11) from Saudi Arabia, a similar coverage rate of 55.5% was reported for the 7-valent conjugate vaccine against invasive infections. However, other studies (16,18,24,26,27) have reported variable coverage rates, ranging from low (26%) to high (95%), for invasive pneumococcal isolates.…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Fouda et al (11) from Saudi Arabia, a similar coverage rate of 55.5% was reported for the 7-valent conjugate vaccine against invasive infections. However, other studies (16,18,24,26,27) have reported variable coverage rates, ranging from low (26%) to high (95%), for invasive pneumococcal isolates.…”
Section: Discussionmentioning
confidence: 97%
“…Serotypes causing invasive diseases differ from country to country; therefore, it is of utmost importance to identify the most common serotypes causing invasive diseases and to determine which of these are resistant to antimicrobial agents. Serogroup coverage rate for the 7-valent conjugate vaccine for children has been reported as 78% in the United States of America [9], 75.3% in Greece [10], 71% in England [11], 56% in Gambia [12], and 48.4% in Scotland [13]. Serotypes 1 and 5, which are not found in the 7-valent conjugate vaccine, have been reported to be common serotypes, especially in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…The hemolytic property of pneumolysin has also been shown to be involved in the initial stages of pneumonia, including invasion of the lung tissue and neutrophil recruitment; however, hemolytic activity is not important in facilitating pneumococcal growth in the alveoli (62,63). As serotype 1 disease is associated with pneumonia rather than meningitis in Europe and the United States (26,30) (Table 1), it may be that hemolytically active pneumolysin is not essential for the pathogenesis of certain serotype 1 sequence types, such as ST306. This may mean that there will be less selective pressure to conserve the nucleotide sequences that encode the hemolytic activity of pneumolysin and may allow the mutations we have identified to arise.…”
Section: Discussionmentioning
confidence: 99%